2011
DOI: 10.1186/1745-6215-12-229
|View full text |Cite
|
Sign up to set email alerts
|

Which dressing do donor site wounds need?: study protocol for a randomized controlled trial

Abstract: BackgroundDonor site wounds after split-skin grafting are rather 'standard' wounds. At present, lots of dressings and topical agents for donor site wounds are commercially available. This causes large variation in the local care of these wounds, while the optimum 'standard' dressing for local wound care is unclear. This protocol describes a trial in which we investigate the effectiveness of various treatment options for these donor site wounds.MethodsA 14-center, six-armed randomized clinical trial is being ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The institutional review board of each contributing centre approved the study protocol, which has been published in detail elsewhere. Contrary to this protocol, the group ‘paraffin gauzes’ was renamed ‘gauzes’, because Adaptic ® (Systagenix, Gatwick, UK) was used in all but three patients (in whom Jelonet ® (Smith and Nephew Healthcare, Hull, UK) was applied).…”
Section: Methodsmentioning
confidence: 99%
“…The institutional review board of each contributing centre approved the study protocol, which has been published in detail elsewhere. Contrary to this protocol, the group ‘paraffin gauzes’ was renamed ‘gauzes’, because Adaptic ® (Systagenix, Gatwick, UK) was used in all but three patients (in whom Jelonet ® (Smith and Nephew Healthcare, Hull, UK) was applied).…”
Section: Methodsmentioning
confidence: 99%
“…Dressing adhesion to skin graft donor site, VAS score, and duration of dressing are presented in Table 2. The mean duration of hospitalization in group A was 17.96±1.4 days (range: 15-21 days), group B, 16.43±1.86 days (range: [13][14][15][16][17][18][19][20], and group C, 16.9±1.55 days (range: [14][15][16][17][18][19][20]. This figure was significantly higher in group A compared with group B and C (P<0.05), but there was no significant difference between groups B and C (P=0.6).…”
Section: Resultsmentioning
confidence: 99%
“…A partialthickness wound is created in the skin graft donor site that is healed by re-epithelialization. It takes 10-14 days to complete epithelialization [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…37 Studies have demonstrated that full-thickness wounds in Duroc swine have a tendency toward fibro proliferative scaring, with more fibrosis, pigmentation, and contraction than other swine species. Our model allows for multiple biologic samples per wound as well as multiple wounds per animal.…”
Section: Discussionmentioning
confidence: 99%